Presentation of a new instrument for assessment of nutritional status in elderly persons: Development of nutrition risk assessment tool - PAVLOVIĆ, JELENA P; Ivković, Nedeljka; Hadživuković, Natalija; Živanović, Srdjan; Pavlović, Kristina (PONS - medicinski časopis, 2026)
International team of experts, Jelena Pavlović, PhD (Faculty of Medicine in Foča, University of East Sarajevo) i Maja Račić, PhD (The Ohio State University, Columbus, United States) constructed and validated a new instrument/tool ​​for nutritional risk assessment in older adults in Bosnia and Herzegovina (Nutrition risk assessment in older adults - NRA). The newly developed tool is comprehensive, has acceptable validity and internal consistency. It contains a total of 14 questions. The scoring of each question as well as the final score of the tool is designed in detail, and the maximum number of points is 21. The tool has three categories, and a lower score indicates a nutritional risk. The time required to complete the assessment ranged from 15 to 22 minutes. the new tool is the author's original contribution to science and practice. The new tool is protected and copyrighted, and can only be used with the author's permission.
Keywords: Development; new instrument; older adults; nutritional risk